Perjudian Online - Falah, Muhammad Fajrul; Tanuwijaya, Fanny; Samosir, Samuel SM (University of Jember, 2017)
Law Number 11 / 2008 on Information and Electronic Transaction (UU ITE) is the regulation concerning on criminal law in addition to the Criminal Code (KUHP). UU ITE is commonly regarded additional regulation of the Criminal Code as a special law (lex specialis) in which Penal Code is deemed as lex generalis. It is based on the principle of lex specialis derogate legi generalis. This article uses legal research to review the decision of District Court in Bandung Number 1033/PID.B/2014/PN.BDG where it comprises legislation and cases. It concludes that the judge is not frugal in applying the principle lex specialis derogat legi generalis in the consideration. This is associated with the indictment of public prosecutor which only prejudges with article 303 paragraph (1) to 2. In contrast, the indictment which does not meet the requirement of a careful, clear, and complete description asserts to become void by law. Keywords: Online Gambling, Criminal Principle, Indictment